A Diffuse Leptomeningeal Glioneural Tumor Case Producing Hydrocephalus and Polyradiculopathy - Picarelli, Helder; Nepomuceno, Thales Bhering; Ribeiro, Renan Ribeiro; Yamaki, Vitor Nagai; Figueiredo, Eberval Gadelha (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
The present report describes the case of a male 17-year-old patient who progressively developed a hydrocephalus and polyradiculopathy due to involvement of central nervous system (CNS) by a diffuse leptomeningeal glioneuronal tumor (DLGNT). The tumor had partial remission in response to the treatment with radiotherapy plus procarbazine, lomustine, and vincristine (PCV) chemotherapy, and the patient had improvement in function and pain levels. The current knowledge about DLGNT, including its clinical manifestations, imaging findings, histological characteristics, and treatment are revised and discussed in the present paper.
Keywords: leptomeningeal glioneuronal tumor; polyradiculopathy; hydrocephalus; oligodendroglial-like leptomeningeal tumor of childhood; PCV chemotherapy